Staphylococcus aureus wraps around Candida albicans and synergistically escapes from Neutrophil extracellular traps - Jing, Qi; Liu, Rui; Jiang, Qingsong; Liu, Yingshuang; He, Jinzhi; Zhou, Xuedong; Yu, Ollie Yiru; Chu, Chun-Hung; Cheng, Lei; Ren, Biao; Li, Mingyun (Frontiers in Immunology, 2024)
NETs, a unique neutrophil immune mechanism, are vital in defending against microbial invasions.Understanding the mechanisms of co-infection by Candida albicans and Staphylococcus aureus, which often leads to higher mortality and poorer prognosis, is crucial for studying infection progression. In our study, we established a mouse model of subcutaneous infection to characterize the inflammation induced by co-infection. By purifying and extracting NETs to interact with microorganisms, we delve into the differences in their interactions with various microbial species. Additionally, we investigated the differences in NETs production by neutrophils in response to single or mixed microorganisms 2 through the interaction between neutrophils and these microorganisms. Furthermore, we analyzed the gene expression differences during co-infection using transcriptomics. In vivo, C. albicans infections tend to aggregate, while S. aureus infections are more diffuse. In cases of co-infection, S. aureus adheres to and wraps C. albicans. NETs exhibit strong killing capability against C. albicans but weaker efficacy against S. aureus. When NETs interact with mixed microorganisms, they preferentially target and kill the outer layer of S. aureus. In the early stages, neutrophils primarily rely on phagocytosis to kill S. aureus, but as the bacteria accumulate, they stimulate neutrophils to produce NETs.Interestingly, in the presence of neutrophils, S. aureus promotes the proliferation and hyphal growth of C. albicans. Our research has showed substantial differences in the progression of co-infections compared to single-microbial infections, thereby providing scientific evidence for NETs as potential therapeutic targets in the treatment of co-infections.